An evaluation of prefilled insulin pens: a focus on the Next Generation FlexPen(®) - Davis, Estella M (Dove Medical Press, 2010)
Insulin pen delivery systems are preferred by patients over the traditional vial and syringe method for insulin delivery because they are simple and easy to use, improve confidence in dosing insulin, and have less interference with activities and improved discretion with use. Insulin manufacturers have made numerous improvements to their first marketed pen devices and are now introducing their next generation of devices. Design modifications to the newest generation of prefilled insulin pen devices are intended to improve the ease of use and safety and continue to positively impact adherence to insulin. This review focuses on the Next Generation FlexPen(®) with regard to design considerations to reduce injection force, improve accuracy and ease of use, and evaluate the preference of patient and health-care provider compared with other disposable, prefilled insulin pen devices.